COVID-19 Associated Contact Restrictions in Germany: Marked Decline in Children's Outpatient Visits for Infectious Diseases without Increasing Visits for Mental Health Disorders - Mara Barschkett; Berthold Koletzko; C. Katharina Spiess (Children, 2021)
Children have a low risk for severe COVID-19 infections, but indirect consequences of the pandemic may affect their health. We evaluated nationwide data on children's outpatient visits before and during the first wave of the COVID-19 pandemic in Germany. Data from the National Association of Statutory Health Insurance Physicians for all children with statutory health insurance and at least one physician's office visit between January 2019 and June 2020 were evaluated for total visits and selected diagnoses for the 2nd quarter of 2019 (8.29 million children, controls) and the 2nd quarter of 2020 (8.5 million, pandemic). Outpatient visits per child fell by 18% during the first wave of the pandemic. Outpatient visits associated with diagnosed infections fell markedly by 51%, particularly for children up to age 5 years for gastroenteritis (73%), otitis media (71%), and streptococcal angina (78%). Outpatient visits for diagnosed chronic physical disorders (diabetes, celiac disease, and hay fever) and mental and behavioral disorders showed little change. Reduced contact between children appears to markedly reduce infection transmission. Infection risks in educational settings should be attenuated after the pandemic through targeted education and counseling and appropriate relationship prevention measures to improve quality of life and opportunities for children and to reduce stress and lost work time for parents.
Keywords: 330; COVID-19; infectious disease transmission; mental health; school closures; day care center closures